100% Love Indonesia: Role of Government Campaign to Promote Local Products in Indonesia - Salehudin, Imam (UI Scholars Hub, 2021)
This research aims to investigate the role of government buy-local campaign to increase consumer willingness to purchase local products in Indonesia. This paper also aims to identify relevant mediating variables between exposure to ¡°buy local¡± campaign and willingness to purchase local products. This research use questionnaire data from 394 respondents selected using purposive sampling method. Product specific constructs are asked and analyzed separately in four different product categories (e.g. Produce, Leather, Culinary and Creative products). Data was analyzed using Structural Equation Model and compared further between product categories. The study found that exposure to the buy local promotion campaign does increase consumer ethnocentrism, attitude toward the campaign and toward domestic products. Consumer ethnocentrism does increase attitude toward domestic product and willingness to purchase local products.